Perlindungan Hukum Bagi Kreditur dalam Permohonan Penundaan Kewajiban Pembayaran Utang (PKPU) atas Timbulnya Perselisihan Nilai Tagihan dengan Nilai yang Ditetapkan oleh Tim Pengurus PKPU - Aji, Nugroho Bayu; Syam, Radian (Neolectura, 2025)
Suspension Of Debt Payment is a legal mechanism regulated in Law No. 37 of 2004, concerning Suspension Of Debt Payment (PKPU) and Bankruptcy, this mechanism allows Creditors and Debtors to apply for postponement of payment of overdue debts through the Commercial Court. This research aims to provide a comprehensive overview of the objection mechanism that can be submitted by Creditors in the event of a dispute between the value of the bill and the value determined by the Management. This research uses normative legal research methods. The results of this study indicate that when the PKPU application has been granted, the Debtor will be in a temporary PKPU condition which lasts for 45 days then the Panel of Judges will appoint Supervisory Judges and Administrators who are tasked with overseeing the PKPU process. In the PKPU series, there are agendas held by the Administrators, one of which is bill matching, in this agenda there is often a dispute between the value of the bill submitted by the Creditor and the value of the bill determined by the Administrators, which if there is such an event then referring to article 279 paragraph 2 of Law No. 37 of 2004, the Creditor can file an objection through the Supervisory Judge, then based on article 280 of Law No. 37 of 2004, the Supervisory Judge will issue a determination which then becomes a reference for the Management in determining the value of the bill from the Creditor which can be included in the PKPU process. This research also includes the determination in case Number: 125/Pdt.Sus-PKPU/2021/PN.Niaga.JKT.PST, in which case, both the Creditor and the Supervisory Judge have carried out the mechanism as regulated in Article 279 paragraph (2) and Article 280 of Law No. 37 of 2004.